Awareness Of Ionizing And Nonionizing Radiation And Their Effects In Medical Students - Ramzan, Ameena; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2023)
Background: The majority of patients are still anxious about exposure to radiation and the risks it poses to their health. A doctor is someone who can answer all of their patients’ queries about radiation and make them happy. This competence may be acquired by medical students during their clinical rotation in the radiology department. The objective of this study is to test medical students’ knowledge, risks, ambiguities, and assumptions about equipment that uses ionizing and non-ionizing radiation. Methods: A questionnaire was self-administered to medical students of a private university of Gujrat. One hundred students included in the study. Final year students who had completed their clinical rotation in the radiology department were included in the study. Also students of third year were also included. The obtained data was analyzed using statistical software. Conclusion: The majority of medical students in both years have little awareness of different features of radiation sources, the risks associated with them, and how to protect themselves from them specially student do not know about the early and late effects associated with radiations. For medical students studying radiography, better teaching techniques and programmes are essential.